Nitrogen Fixation in Cereals - Rosenblueth, Mónica; Ormeño-Orrillo, Ernesto; López-López, Aline; Rogel, Marco A.; Reyes-Hernández, Blanca Jazmín; Martínez-Romero, Julio C.; Reddy, Pallavolu M.; Martínez-Romero, Esperanza (Frontiers in Microbiology, 2018)
Cereals such as maize, rice, wheat and sorghum are the most important crops for human nutrition. Like other plants, cereals associate with diverse bacteria (including nitrogen-fixing bacteria called diazotrophs) and fungi. As large amounts of chemical fertilizers are used in cereals, it has always been desirable to promote biological nitrogen fixation in such crops. The quest for nitrogen fixation in cereals started long ago with the isolation of nitrogen-fixing bacteria from different plants. The sources of diazotrophs in cereals may be seeds, soils, and even irrigation water and diazotrophs have been found on roots or as endophytes. Recently, culture-independent molecular approaches have revealed that some rhizobia are found in cereal plants. Since the levels of nitrogen-fixation attained with nitrogen-fixing bacteria in cereals are not high enough to support the plant’s needs and never as good as those obtained with chemical fertilizers or with rhizobium in symbiosis with legumes, it has been the aim of different studies to increase nitrogen-fixation in cereals. As a general rule, these efforts have not been successful. However, new diazotroph mutants with enhanced capabilities to excrete ammonium are being successfully used to promote plant growth as commensal bacteria. In addition, there are ambitious projects supported by different funding agencies that are trying to modify maize and other cereals genetically to fix nitrogen or to form nodules with nitrogen-fixing symbiotic rhizobia.